Charting the coevolution of cyberprotest and counteraction: The case of former Soviet Union states from 1997 to 2011. (May 2014) - Lysenko, Volodymyr V; Desouza, Kevin C
The authors systematically investigate the evolution of the modern information and communication technologies (ICTs) and the associated changes in protest – related tactics employed by two main stakeholders in the contemporary contentious political processes – dissenters and incumbent political authorities. Through in-depth investigation of the cyberprotest cases in the former Soviet states of Belarus, Moldova, Russia, and Ukraine, which occurred during the last decade, a coherent outline is developed of the co-evolution of the ICT-enabled protest tactics of the main counterparts in the contemporary political struggle in these countries. Particularly, it was found that there were at least three highly distinguishable levels of development of modern ICTs and the associated types of protest-related tactics employed by the main stakeholders in these events. It was established that as soon as the authorities were able to effectively counteract the previous ICT-enabled tactics by the dissenters, new developments in modern ICTs always empowered the latter to devise new effective strategies to overcome previously successful counterrevolutionary measures of the political authorities.